Fisetin Prevents Acetaminophen-Induced Liver Injury by Promoting Autophagy - Zhang, Jiaqi; Zhao, Licong; Hu, Cheng; Wang, Tao; Lu, Juan; Wu, Chenqu; Chen, Long; Jin, Mingming; Hu, Hao; Ji, Guang; Cao, Qin; Jiang, Yuanye (Frontiers in Pharmacology, 2020)
Acetaminophen (APAP) overdose is a leading cause of drug-induced acute liver failure in clinical and hospital settings. Fisetin (FST) is a phenolic compound derived from natural products such as fruit and vegetables. Our research investigated the protective mechanisms of FST in APAP-induced hepatic injury in vitro and vivo. Assessment of mouse serum levels of alanine/aspartate aminotransferases (ALT/AST), liver myeloperoxidase (MPO) activity, malondialdehyde (MDA), glutathione (GSH) and reactive oxygen species (ROS) demonstrated the protective effects of FST towards APAP-induced liver injury. FST also reversed an APAP-induced decrease in mouse L-02 cell line viability. Our results also showed that FST significantly promoted APAP-induced autophagy and inhibited inflammasome activation both in vivo and in vitro. We also found that silencing ATG5, using si-ATG5, reduced the protective effects of FST against APAP-induced hepatotoxicity and reversed the effects on autophagy. Finally, we used the autophagy inhibitor, 3-methyladenine (3-MA) to validate the involvement of autophagy in FST against APAP-induced hepatotoxicity in vitro. We demonstrated that FST prevented APAP-induced hepatotoxicity by increasing ATG5 expression, thereby promoting autophagy and inhibiting inflammasome activation.